(untitled) (INNOVATIVE ECONOMY, 2020)
Shkolnyi O.O. THE DEVELOPMENT OF “GREEN” MARKETING IN THE FOOD RETAILING INDUSTRY Purpose. The aim of the article is the reflection of the European experience in developing ecologically oriented marketing which can be prerequisite of strategic positioning and strengthening global competitive advantage for the food retailing industry. Methodology of research. Investigations of outstanding domestic and foreign scientists have been considered as the theoretical basis of current study. General scientific and special methods are used in the process of research, in particular: method of statistical analysis, synthesis and graphic method were used as methodological tools for highlighting innovative aspects of food marketing. Findings. It was found that today consumers are increasingly focusing on compliance with the methods of production and goods selling according to the environmental requirements. It is determined that the public interests require strict responsibility regarding to the socioeconomic and environmental impacts of organizations. It is established that the tendencies of increasing demand for food produced by dynamically adaptive and environmentally sustainable technologies with minimal usage of non-renewable inputs and energy resources from non-agricultural origin testify the consumers’ support for technologies that are reflecting ecological objectives and not harmful to the environment. Thanks to innovative technologies, Germany holds sustainable competitive positions in developing marketing. It is established that the company Schwarz-Gruppe GmbH that owns the Lidl and Kaufland brands is a powerful player in the European market. The concerns related to the climate change, increasing energy prices and the depletion of natural resources have been strengthening Lidl’s incentives to implement measures towards sustainable development. This company actively utilizes the principles of innovative environmentally friendly business and applies environmentally protective requirements to technologies and the physical capital. It is determined that the global competitive advantage for the food retail industry can be supported by the effective technological monitoring in “green” marketing, the development of innovation culture, ensuring high quality standards and attracting new business solutions to the “green” logistics. Originality. The combination of the innovative technologies in "green" marketing and business solutions in the environmentally oriented logistics was identified as prerequisite for innovative transformations and achieving global competitive advantage for the food retail industry. Practical value. The obtained results of the synthesis of the European experience create the basis for improving the domestic organizational and economic mechanism of managing environmentally oriented marketing in the retail food industry. Key words: food retailing industry, innovative technologies, organic food, “green” marketing, environmentally oriented logistics, competitiveness.